2007
DOI: 10.1007/s10493-007-9058-1
|View full text |Cite
|
Sign up to set email alerts
|

ITS2 sequences as barcodes for identifying and analyzing spider mites (Acari: Tetranychidae)

Abstract: The use of DNA barcodes, short DNA sequences from a standardized region of the genome, has recently been proposed as a tool to facilitate species identification and discovery. Here we show that second internal transcribed spacer of nuclear ribosomal DNA (rDNA-ITS2) barcodes effectively discriminate among 16 species of spider mites (Acari: Tetranychidae) from Israel. The barcode sequences of each species were unambiguously distinguishable from all other species and formed distinct, nonoverlapping monophyletic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
93
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 25 publications
15
93
0
1
Order By: Relevance
“…Analyses of the sequences (Alvarez and Wendel 2003;Webster et al 2004;Marrelli et al 2006;Thanwisai et al 2006;Ben-David et al 2007) showed that such a method could be potentially used to identify astigmatid mites with similar morphological characteristics. When the mites were cloned, as in B. tropicalis described here, few or no differences were observed in their ITS2 regions.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of the sequences (Alvarez and Wendel 2003;Webster et al 2004;Marrelli et al 2006;Thanwisai et al 2006;Ben-David et al 2007) showed that such a method could be potentially used to identify astigmatid mites with similar morphological characteristics. When the mites were cloned, as in B. tropicalis described here, few or no differences were observed in their ITS2 regions.…”
Section: Discussionmentioning
confidence: 99%
“…The internal transcribed spacer 2 (ITS2) region of nuclear ribosomal RNA (rRNA) genes (Navajas & Boursot 2003;Noge et al 2005;Ben-David et al 2007) and the cytochrome c oxidase subunit I (COI) gene of Article mitochondrial DNA (mtDNA) (Matsuda et al 2012(Matsuda et al , 2013 have been used to identify spider mite species. Once molecular identification corresponds with morphological identification, it can be used to determine species rapidly and without a need for expertise in morphology.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the genetic structure of populations of T. urticae in citrus groves appears as a powerful approach to estimate gene flow among mites infesting different plants in the agroecosystem. Different molecular techniques, such as microsatellite markers, isolated in T. urticae and other related mite species (Navajas et al 1998a(Navajas et al , 2000Nishimura et al 2003, Uesugi et al 2007, Abercrombie et al 2009and Hinomoto et al 2010, and the sequence of mitochondrial DNA gene coding for cytochrome oxidase I (COI) have already been used in tetranychid mites to study both inter-and intraspecific variation among populations (Navajas, 1998;Navajas et al 1998bNavajas et al , 1999Navajas et al , 2000Navajas and Fenton 2000;Hinomoto and Takafuji 2001;Tixier et al 2002a,b;Bailly et al 2004;Xie et al 2006;Ben-David et al 2007;Carbonelle et al 2007;Uesugi et al 2009a,b;Li et al 2009). Microsatellite markers have become one of the most popular genetic markers and they have been chosen in ecological studies because of their high polymorphism.…”
Section: Introductionmentioning
confidence: 99%